Peran Sosial Perguruan Tinggi Islam dalam Program Campus Social Responsibility - Musrifah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2023)
CSR (Corporate Social Responsibility) has long been known in the industrial world in the form of social activities as a form of responsibility for the utilization and management of natural resources by state-owned enterprises. In its development, CSR has also become one of the marketing communication strategies by various industries and non-governmental institutions. Besides providing benefits in social contributions, CSR also has a major impact in expanding and strengthening corporate branding. With a strong and broad branding, the public's positive perception of the company can increase. With this spirit, the campus as an educational institution that cannot be separated from its social role can actually carry out the CSR function. This Campus Social Responsibility idea can be actualized into six forms of CSR as formulated by Philip Kotler and Nancy Lee, namely: (1) Cause Promotions, (2) Cause Related Marketing, (3) Corporate Social Marketing, (4) Corporate Philanthropy, (5 ) Community Volunteering, and (6) Social Responsibility Business Practices. By implementing CSR, it is hoped that the branding as an independent and moderate campus can be realized automatically.